Antisense DNA downregulation of the ERBB2 oncogene measured by a flow cytometric assay. - Vaughn, J P (1995)
A causal role has been inferred for ERBB2 overexpression in the etiology of breast cancer and other epithelial malignancies. The development of therapeutics that inhibit this tyrosine kinase cell surface receptor remains a high priority. This report describes the specific downregulation of ERBB2 protein and mRNA in the breast cancer cell line SK-BR-3 by using antisense DNA phosphorothioates. An approach was developed to examine antisense effects which allows simultaneous measurements of antisense dose and gene specific regulation on a per cell basis. A fluorescein isothiocyanate end-labeled tracer oligonucleotide was codelivered with antisense DNA followed by immunofluorescent staining for ERBB2 protein expression. Two-color flow cytometry measured the amount of both intracellular oligonucleotide and ERBB2 protein. In addition, populations of cells that received various doses of nucleic acids were physically separated and studied. In any given transfection, a 100-fold variation in oligonucleotide dosage was found. ERBB2 protein expression was reduced greater than 50%, but only in cells within a relatively narrow uptake range. Steady-state ERBB2 mRNA levels were selectively diminished, indicating a specific antisense effect. Cells receiving the optimal antisense dose were sorted and analyzed for cell cycle changes. After 2 days of ERBB2 suppression, breast cancer cells showed an accumulation in the G1 phase of the cell cycle.